(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The study analyzed the prose of the famous Austrian writer, Joseph Roth (1894–1939), dedicated to the First World War in its existential dimensions. The leitmotif of the author’s artistic and journalistic universe is the destruction of the old world, the collapse of the Austro-Hungarian Empire, the decay of the existing system of cultural references, and the impact of history and fate on the individual. The era of historical cataclysms reformats time and space. In particular, Roth’s characters want to live in the past; they have nostalgia for the lost «golden age», which, in fact, is a myth of monarchy. The broad social panorama created by the writer let the reader track a new identity searched for by members of different social groups.